2018
DOI: 10.3390/ma11040483
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Flame Retardant Polyacrylonitrile Fabric Based on Sol-Gel and Layer-by-Layer Assembly

Abstract: This paper aims to develop a novel method, i.e., sol-gel combined with layer-by-layer assembly technology, to impart flame retardancy on polyacrylonitrile (PAN) fabrics. Silica-sol was synthesized via the sol-gel process and acted as cationic solution, and phytic acid (PA) was used as the anionic medium. Flame-retardant-treated PAN fabric (FR-PAN) could achieve excellent flame retardancy with 10 bilayer (10BL) coating through layer-by-layer assembly. The structure of the fabrics was characterized by X-ray phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 39 publications
(45 reference statements)
2
21
0
Order By: Relevance
“…The sol-gel process has been extensively studied in recent years for flame-retardants [24][25][26][27]. Synthesis is based on two-step reactions, i.e., hydrolysis (converted to unstable hydroxides) and condensation (formation of covalent bonds) of a metal-organic precursor such as an alkoxide, tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), and titanium tetraisopropoxide (TTIPO) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel process has been extensively studied in recent years for flame-retardants [24][25][26][27]. Synthesis is based on two-step reactions, i.e., hydrolysis (converted to unstable hydroxides) and condensation (formation of covalent bonds) of a metal-organic precursor such as an alkoxide, tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), and titanium tetraisopropoxide (TTIPO) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical compositions of PAN, PVA/PAN, C-PVA/PAN, and FR-PVA/PAN were analyzed by XPS, as shown in Figure 2 and Table 2. The four samples all contained C 1s , N 1s , and O 1s , corresponding to the peaks at 300 eV, 409 eV, and 543 eV, respectively [11,12,13]. Compared with PAN fiber, the PVA/PAN fiber showed an increase of the oxygen element from 10.86% to 14.28%.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the C-PVA/PAN fiber, the peak at 191 eV was assigned to B 1s [20]. For FR-PVA/PAN, a new peak at 131 eV, assigned to P 2p [11,12,13], clearly appeared. Thus, it can be concluded that the chemical modification of C-PVA/PAN with phosphoric acid was successful.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations